ONLINE MATHEMATICS LEARNING USING MEDIA IN CLASS VII MTs DARUL HIKMAH PEKANBARU - Sri Indriyani; Dewi Rahmat (Jurnal Prinsip Pendidikan Matematika, 2021)
Coronavirus Disease-2019 (Covid-19) as a pandemic has consequences in various fields such as health, social, political, economic, and educational. The government's recommendation in the context of preventing Covid-19 has led to various new regulations, especially in the education sector. One of the policies from circular letter number 4 of 2020 by the Minister of Education and Culture of the Republic of Indonesia regarding the Implementation of Education Policies in the Emergency Period for the Spread of Covid-19 is to explain that the learning process is carried out at home via online/remotely. In conditions of online learning (on a network/online) during the covid-19 pandemic, an educator needs more appropriate learning media so that students can learn optimally. The purpose of this study was to determine the results of the evaluation of student learning by using appropriate mathematics learning media in the form of learning videos either made by the teacher or via a youtube link. The type of this research used qualitative descriptive method. The subjects of this study were students of class VIII and VIIH MTs Darul Hikmah Pekanbaru. The data collection techniques included: observation, interviews, and documentation. Based on the result of the research that had been done, it can be concluded that learning without using the right media appeared that students' understanding of the material was still lack. It can be seen from the responses of students in the classroom based on the result of the researcher observations during the study.